# How do i solve x (2 + 5) = (5 x 2) + (5 x 5) ?

Relevance
• x(2+5) = (5 x 2) + (5 x 5)...(1);

Case 1: (5 x 2) means 5x^2 and (5 x 5) means 5x5;

Then (1) means 7x = 5x^2 + 5x^5, ie., 7x = (5x^2)(1+ x^3);

Case 2: (5 x 2) means (5*2) and (5 x 5) means (5*5);

Then (1) means 7x = (5*2) + (5*5) = 5(2+5) = 7*5;

Summary: Use (^) to denote ''raised to the power'' as in 2^3 = 8;

.................Use (*)  to denote ''times'' as in 7*9 = 63;

If you wished to remove any possibility of ambiguity, you would have written either;

7x = 5x^2 + 25 or 7x = (5*2) + (5*5);

Formats such as (5 x 2) and (5 x 5) are meaningless.

• Remember themaths rule ; 'Do inside the brackets first'.

x(7)  = (10) + (25)

Remove the brackets

7x = 10 + 25

7x = 35

Divide both sides by '7'

7x/7 = 35/7

x = 5

•  x (2 + 5) = (5 x 2) + (5 x 5)

x = 5

• x (2 + 5) = (5 x 2) + (5 x 5)

x(7) = 10 + 25

7x = 35

7x/7 = 35/7

x = 5

• To avoid confusion it would be best to write this as

x*(2 + 5) = (5 * 2) + (5 * 5)

7x = 10 + 25 = 35

x = 5

• Does the first “x” mean something different than the “x” between the 5 and the 2? Please use “*” for multiplication.

• x(2 + 5) = (5 x 2) + (5 x 5)

7x = 10 + 25

7x = 35

(7x/7) = 35/7